SACS-2/SMASH – Validation Report on the Eyjafjallajökull and Grimsvötn eruptions - Koukouli, MariLiza; Balis, Dimitris; Dimopoulos, Spiros; Siomos, Nikos (Zenodo, 2014)
The main objective of the SACS-2/SMASH project is to create an optimal End-to-End System for Volcanic Ash Plume Monitoring and Prediction . This system is based on improved and dedicated satellite-derived ash plume and sulphur dioxide level assessments, as well as an extensive validation using auxiliary satellite, aircraft and ground-based measurements. The focus of the LAP/AUTH satellite data validation activities is to validate SO 2 and ash characteristics products provided by different satellite instruments during the following eruptions: 15 to 26 April 2010, Eyjafjallajökull, Iceland. 4 to 20 May 2010, Eyjafjallajökull, Iceland. 21 to 28 May 2011, Grimsvötn, Iceland. The validation was performed on two levels, on the total SO 2 column assessment, discussed in length in Section 2, and on the ash plume characteristics, i.e. the aerosol optical depth and, where applicable, the ash plume height, presented in Sections 3, 4 and 5. A short section on satellite-to-satellite inter-comparison is given both in sub-section 2.7 for the SO 2 products as well as in Section 6 for all different ash products.